Climate Change Law in China in Global Context - He, Xiangbai; Zhang, Hao; Zahar, Alexander (Routledge Advances in Climate Change Research, 2020)
In Climate Change Law in China in Global Context, seven climate change law scholars explain how the country’s legal system is gradually being mobilized to support the reduction of greenhouse gas emissions in China and achieve adaptation to climate change. There has been little English scholarship on the legal regime for climate change in China. This volume addresses this gap in the literature and focuses on recent attempts by the country to build defences against the impacts of climate change and to meet the country’s international obligations on mitigation. The authors are not only interested in China’s laws on paper; rather, the book explains how these laws are implemented and integrated in practice and sheds light on China’s current laws, laws in preparation, the changing standing of law relative to policy, and the further reforms that will be necessary in response to the 2015 Paris Agreement on Climate Change. This comprehensive and critical account of the Chinese legal system’s response to the pressures of climate change will be an important resource for scholars of international law, environmental law, and Chinese law.